Investigating the role of local angiotensin system in the browning of white adipocytes - Tan, Shi Wei (2015)
The renin-angiotensin system (RAS) serves a critical role in regulating energy balance, rendering it a potential target for treating obesity and its comorbidities. Angiotensin peptides involved in the RAS are believed to have autocrine effects on adipose tissue, which produces all the components of the RAS. In our present study, we endeavored to find whether the RAS in adipose tissue could engender browning characteristics by looking at the effects of angiotensin II (Ang II) and angiotensin 1-7 (Ang 1-7) on WAT, and to bring about further understanding of the unique role of the RAS in adipose tissue. 3T3 L1 cells were treated with or without a. Ang II; b. ZD7155, an antagonist for the angiotensin type 1 (AT1) receptor; c. Ang II + ZD7155; d. PD123319, an antagonist for the angiotensin type 2 (AT2) receptor; e. Ang II + PD123319; f. A779, an antagonist for Mas receptor; and g. Ang (1-7) + A779, over a period of 3 – 4 days. Our results show that Ang II action on AT2 significantly increased the expression of brown-specific proteins and transcription factors UCP 1, CIDE-A and PGC-1α. Likewise, Ang 1-7 action on Mas receptor also increased the expression of UCP 1, CIDE-A, PGC-1α and PRDM16. These results support the hypothesis that Ang II-AT2 and Ang (1-7)-Mas receptor interactions promotes browning characteristics in white adipocytes, at least in part by stimulating the expressions of PGC1α. The findings of this study may provide a novel route to combat obesity and associated metabolic diseases.